Pascal and HTML Programming Extracurricular Activities at Budi Mulia High School - Haris, Darius Andana; Chung, Cecillia (Dinasti International Journal of Education Management and Social Science, 2025)
The extracurricular programming program focusing on Pascal and HTML at Budi Mulia High School represents a strategic initiative to equip students with foundational skills in information technology, addressing the rapid advancements in this field. Designed to introduce structured programming principles through Pascal and static web development using HTML, the program employs a blended theoretical-practical pedagogical approach, emphasizing project-based learning (PBL) to foster creativity and problem-solving competencies. Conducted from January to February 2025, the program yielded significant improvement in students’ proficiency. In Pascal programming, 85% of participants demonstrated mastery of fundamental syntax, conditional structures (e.g., IF-ELSE and CASE statements), and iterative constructs (including FOR, WHILE, and REPEAT loops). A notable achievement was their successful implementation of a star-pattern simulation using the gotoxy command. Meanwhile, in web development, 90% of students completed static web projects employing HTML and CSS, exemplified by their creation of responsive class organizational structure webpages. The program’s positive outcomes include measurable improvement in computational logic, collaborative problem-solving, and readiness for advanced programming studies. These results underscore the efficacy of integrating structured programming and web development into secondary education curricula as a means of cultivating digital literacy and preparing learners for future technological challenges.